Women´s expectations and evaluation of a maternal educational program (Colombia Medica, 2013)
Objectives: To identify the expectations of women requesting the maternal education program (ME) and to determine their evaluation of it.Methods: a multi-centric observational study was conducted in four hospitals in Spain in 2011 with primiparous women.  Socio-demographic and obstetrical variables, among others, were collected through interviews and reviews of medical records.  The analysis estimated crude and adjusted odds ratios using logistic regression with a confidence interval of 95%.Results: Newborn care was most requested type of content desired by women (80.33%).  Eleven and one quarter percent (11.25%) of the women evaluated ME as being of little or no usefulness or benefit. Women appreciated the follow-up care given during pregnancy and childbirth but ME was not noted as influencing the measurement of these processes (p> 0.05).Conclusions: Newborn care was the type of subject mainly demanded by the women in the ME program.  Women evaluated ME as being a useful program.